Determinants of women empowerment: Case of refugee women living in Nairobi Kenya - Judy Kaaria; Immaculate Kathomi Murithi (Economies, 2025)
This study investigates the determinants of women empowerment among refugee women living in Nairobi, Kenya. First, the study constructs an index to examine empowerment drivers using data from the Refugee and Host Household Survey (RHHS) 2021. A fractional logit regression model was employed in the study. The results obtained show that the incidence of refugee women empowerment among refugees living in Nairobi was six percent. In addition, the study finds evidence that age; the gender of the household head; the education level of the refugee woman; employment status; and the education of the household head play substantial roles in enabling women empowerment. Conversely, marital statuses (divorced/separated/widowed and single/never married) and religious affiliations (Muslim) hinder women empowerment. Efforts geared towards improving wage employment and education are likely to empower refugee women. The study emphasizes the recognition of the role played by women in household income through care work.
Keywords: D63; F22; C43; J13; J15; J16; 330; women empowerment; refugee women; empowerment index; gender